Penghutanan bandar dan kesihatan ekosistem lembangan: Pengalaman dari St Helens, United Kingdom - Noorazuan Md Hashim, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
Before the Industrial Revolution in the nineteenth century, St Helens (which is located at the centre of Sankey catchment) was only a small village located at the junction of the boundaries of four townships - Windle, Sutton, Eccleston and Parr. The opening of ship canals as well as the development of the transportation network between Liverpool and Manchester had also increased urban sprawl in the Sankey catchment. Alteration of the river characteristics as a result of urbanisation since 200 years ago has led to several hydrological changes and severe problems in urban catchments, such as water pollution and flash floods. Since the late 1980s, urban renewal programmes have been implemented in the Sankey catchment by various agencies, focusing the urban greening effort on Sankey’s river corridor and also upgrading the derelict and ‘brownfields’ land. It is evident that the Sankey catchment has had differences in hydrological responses over time. The most significant finding is the change of flow characteristics between 1987 and 1996. The 1987-1996 period showed how the succession of urban renewal programmes increased the health of the catchment’s ecosystem. Non-structural measures such as public-private cooperation with public participation in the urban regeneration programmes of the Sankey catchment, especially in the St Helens has proved that it succeeded in improving the urban water quantity characteristics as well as water quality within a decade. The late urbanisation stage in Sankey shows a dominance of reconstruction or redevelopment of the urban area rather than the increase in urban imperviousness